Pension funds' performance in strongly regulated industries in Central Europe: Evidence from Poland and Hungary - Martin T. Bohl; Judith Lischewski; Svitlana Voronkova (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2010)
This paper presents an analysis of pension funds' performance in Poland and Hungary, two Central European countries characterized by strong regulation of their private pension fund industries. Thus, the paper extends the literature which has so far mostly focused on performance of pension fund industries facing no or limited regulation. We find that the performance of pension funds in the two studied countries differs. While we do not find convincing evidence of outperformance by Polish pension funds, we find strong evidence of underperformance by Hungarian pension funds. The results are robust to time-variation. The paper considers possible explanations behind these findings. The results of the paper should be of interest for policy-makers seeking to achieve optimal performance of the pension systems and academics in the research area of pension funds.
Keywords: G23; G28; 330; pension fund management; investment and performance regulation; performance measurement; Central European stock markets; Emerging Markets; Pensionsfonds; Regulierung; Wirkungsanalyse; Unternehmensentwicklung; Polen; Ungarn